Response of host immune system to tick borne encephalitis virus - Iveta Stibraniova; Pavlina Bartikova; Jozef Dzubara (Acta Virologica)
Tick-borne encephalitis virus (TBEV, Flaviviridae), a small enveloped flavivirus with an unsegmented positive-stranded RNA genome, is the most prominent member of the mammalian group of tick-borne flaviviruses. TBEV, originally isolated in 1937, is identified as Orthoflavivirus encephalitidis now. TBEV causes the most important arboviral disease of the human central nervous system (CNS) in Europe and Northeast Asia. It is transmitted to hosts primarily by ticks of the genus Ixodes and Dermacentor, but can also be acquired by ingestion of infected unpasteurized dairy products. Approximately one-third of all human TBEV infections are associated with severe clinical neurological disease. The remaining two-thirds are asymptomatic or present with mild clinical symptoms. In hosts, TBEV tend to induce different types of immune effector mechanisms. Components of innate immunity - natural killer cells, complement proteins, macrophages and dendritic cells usually provide rapid and intense protection in the acute phase of infectious diseases. In turn, cell-mediated immunity provided by T and B lymphocytes plays an important role in virus clearance and protective immunity, and thus influences the outcome of disease. The virus-host relationship is not passive. Therefore, viruses themselves respond actively to host immune defence activities. This is made possible by a number of mechanisms that ensure their escape from the host’s immune surveillance. The aim of this review is to summarize the history of the last 50 years as well as advances in research on the immunology of TBEV, specifically in the Central European area.